BIOGRAFI SITI MANGGOPOH SEBAGAI SUMBER KEARIFAN LOKAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH (Studi Kasus Pada Siswa MAN Koto Kecil Kabupaten Agam Propinsi Sumatera Barat) - Desi Hilda Sari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The background of this study is there is no local history in history subject which is taugh at the MAN Koto Kecil.The source of data are the head of madrasah, curriculum, history teachers, students, and the people who take the policy related to education in Agam District, West Sumatra Province. The result of the research indicates that the teaching of history subject at MAN Koto Kecil still focuses on the national history.The implemantation of teaching history with local history contents starts when this research conducted and the history teachers committe to teach it for the next history class. Teaching local history by using biography of Siti Manggopoh makes students interest to seek information more deeply about Siti Manggopoh and made her struggle’s values as a role model, so that, it forms the local wisdom in students themselves. The class’ atmosphere more motivates and it can improve student motivation.The obstacles in teaching local history by using Siti Manggopoh’s biography are adequate facility, limitation of local history sources and time, and also the skill of teacher in integrating the local history into national history.